Enhancing IoT security through blockchain integration - Shujaa, Wafa; Alanzi, Mona; Sankaranarayanan, Suresh (Frontiers in Computer Science, 2025)
Blockchain technology has emerged as a potential solution for securing the rapidly expanding Internet of Things (IoT). This review critically analyzes 49 recent scientific publications to assess the current state of blockchain-based IoT security. We examine the strengths and weaknesses of various approaches, focusing on their ability to address data integrity, authentication, and access control vulnerabilities. The review identifies persistent challenges related to scalability, energy efficiency, and privacy, and proposes actionable future research directions. These directions include the development of context-aware security protocols, adaptive trust models, and privacy-preserving analytics techniques. This paper provides a valuable resource for researchers seeking to advance the field of blockchain-based IoT security.